'I remembered this mathematics course because … ': how unforgettable mathematics experiences of pre-service early childhood teachers are related to their beliefs. Issue 2 (7th February 2021) - Öçal, Tuğba
ABSTRACT: Pre-service early childhood teachers' beliefs about mathematics are significant because those beliefs will affect many factors involved in their future teaching. This research explored pre-service teachers' unforgettable mathematics experiences and how these experiences were related to their beliefs about preparing an unforgettable mathematics lesson. This is a case study with conveniently selected participants. Among the participants' previous mathematics experiences, four categories were delineated: teacher, student, material, and method-related issues, although the most common findings were related to their teachers. Regarding beliefs, participants' beliefs are presented within these categories (teacher, student, material, and method-related beliefs) as well as learning environment related beliefs are also found. In addition, McLeod [McLeod, D. B. (1992). Research on affect in mathematics education: A reconceptualization. In D. A. Grouws (Ed.), Handbook of research on mathematics teaching and learning (pp. 575–596). Macmillan] categories for beliefs are also considered in the study. However, none of the participants' beliefs are found to be under McLeod's category of 'beliefs about math.' Therefore, findings indicated that there are both common and conflicting categories and themes with respect to McLeod's categories.